2022
DOI: 10.1108/emjb-12-2021-0194
|View full text |Cite
|
Sign up to set email alerts
|

Factors influence user’s intention to continue use of e-banking during COVID-19 pandemic: the nexus between self-determination and expectation confirmation model

Abstract: PurposeInternet banking services are proven to be much advantageous and convenient during COVID-19 pandemic. However, vibrant networking designs and dynamic changes in software development have made these services bit complex. Thus, the current study seeks to investigate Internet banking user continuance intention with factors underpinning self-determination theory (SDT) and expectation confirmation model (ECM) theory. The moderating role of image is studied between user intention to continue use of Internet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 57 publications
4
22
0
Order By: Relevance
“…These perceptions of usefulness may differ from or coincide with the users’ initial anticipations. The subsequent formation of satisfaction is caused by the confirmation of expectations and the perception of usefulness ( Rahi et al, 2022 ). Finally, a high degree of technical satisfaction will form a continuous intention ( Rabaa'i et al, 2021 ; Anjum et al, 2022 ; Huang et al, 2022 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These perceptions of usefulness may differ from or coincide with the users’ initial anticipations. The subsequent formation of satisfaction is caused by the confirmation of expectations and the perception of usefulness ( Rahi et al, 2022 ). Finally, a high degree of technical satisfaction will form a continuous intention ( Rabaa'i et al, 2021 ; Anjum et al, 2022 ; Huang et al, 2022 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, students with high CSE may have a higher PU of online learning systems. However, low computer self-efficacy students will experience tension and anxiety when using computers, which will lower their judgment of their usefulness ( Rahi et al, 2022 ). Analysis based on the above literature review, the hypotheses are derived as follows:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The estimation of structural model incorporates evaluation of path coefficient, coefficient of determination R 2 , standard error, significance and t -statistics (Rahi, 2021). Nevertheless, lateral collinearity issue must be addressed through variance inflation factors before structural model assessment (Rahi et al , 2022; Rahi et al , 2018). Therefore, results of the lateral collinearity revealed that VIF values of all endogenous factors were less than 3.3, and hence confirming that multi-collinearity is not likely issue in this research.…”
Section: Discussionmentioning
confidence: 99%
“…The theory has been widely used and empirically validated in explaining the post-adoption behaviour of several information systems used in different fields. In the context of this Determinants of continuance intention study, the theory has been used to study mobile government services and e-government services (Hariguna et al, 2020;Mandari and Koloseni, 2021;Rahi et al, 2022;Wijaya et al, 2019). The theory comprises of four key constructs which are confirmation of expectation, satisfaction, perceived usefulness and continuance intention.…”
Section: Expectancy Confirmation Modelmentioning
confidence: 99%